Conservation tillage mitigates drought-induced soybean yield losses in the US Corn Belt. Issue 1 (3rd May 2021) - Chen, Bowen; Gramig, Benjamin M; Yun, Seong D
Abstract: Conservation tillage has been widely recommended for implementation in the U.S. for its environmental benefits. The effect of conservation tillage on crop yield is a subject of continued concern amongst farmers who have not adopted the practice. Previous empirical research on the yield performance of conservation tillage is largely limited to field trials, while observational studies remain scant. This article estimates the effects of conservation tillage on county average corn and soybean yields using remotely-sensed tillage practice adoption data in 646 counties across 12 Corn Belt states from 2005 to 2018. Exploiting deviations from county-specific means in the data, we find no evidence that conservation tillage negatively affects corn or soybean yields. We also find that it can mitigate the impact of drought on soybean yields. We explore how wider use of conservation tillage might offset the increase in drought-induced downside risk to soybean yields under climate change projections from five global climate models.